Hermeneutika Hans-Georg Gadamer dan Relevansinya terhadap Pemahaman Hadis “Keterlibatan Malaikat dalam Hubungan Seksual” - Nafisatul Mu’awwanah (Millati: Journal of Islamic Studies and Humanities, 2018)
This paper deals with Gadamer’s hermeneutical theory and how relevant it is to the study of Islam, which in this case is applied in the hadith “the involvement of angels in sexual relations”. The concept of Gadamer greatly emphasizes the merger of the horizons, the horizon of the text and the horizon of the reader. Merging the horizons will then generate meaningful sense. Meaningful sense is what according to Gadamer, can be applied in the reader. When Gadamer’s hermeneutical theory is applied in the hadith of “the involvement of angels in sexual relations”, a reader of hadith should be able to combine the horizon of the hadith, how it is understood in the time of the Prophet, and the horizon of the reader, the needs and conditions of the present. From the merger, it was found that the meaningful sense of the hadith is “keeping and maintaining harmony of husband and wife relationship”. Meaningful sense of this hadith should be applied in the present, regardless of the nature of the relationship between husband and wife. So Gadamer’s hermeneutical concept can be said to be relevant to eliminate the issues that develop today about gender bias.